Food microbiology laboratory - McLandsborough, Lynne Ann (CRC series in contemporary food science, 2005)
Based on lab experiments developed for food science and microbiology courses at the University of Massachusetts, this manual presents well-tested and outlined experiments for use in a one-semester introductory food microbiology course. It also features 14 exercises that incorporate traditional and rapid method testing techniques